The Rest Is Noise: Listening to the Twentieth Century - Ross, Alex (London Fourth Estate, 2008)
The scandal over modern music has not died down. While paintings by Pablo Picasso and Jackson Pollock sell for a hundred million dollars or more, shocking musical works from Stravinsky's Rite of Spring onward still send ripples of unease through audiences. At the same time, the influence of modern music can be felt everywhere. Avant-garde sounds populate the soundtracks of Hollywood thrillers. Minimalist music has had a huge effect on rock, pop, and dance music from the Velvet Underground onward. Alex Ross, the brilliant music critic for The New Yorker, shines a bright light on this secret world, and shows how it has pervaded every corner of twentieth century life. The Rest Is Noise takes the reader inside the labyrinth of modern sound. It tells of maverick personalities who have resisted the cult of the classical past, struggled against the indifference of a wide public, and defied the will of dictators. Whether they have charmed audiences with the purest beauty or battered them with the purest noise, composers have always been exuberantly of the present, defying the stereotype of classical music as a dying art. Ross, in this sweeping and dramatic narrative, takes us from Vienna before the First World War to Paris in the twenties, from Hitler's Germany and Stalin's Russia to downtown New York in the sixties and seventies. We follow the rise of mass culture and mass politics, of dramatic new technologies, of hot and cold wars, of experiments, revolutions, riots, and friendships forged and broken. In the tradition of Simon Schama's The Embarrassment of Riches and Louis Menand's The Metaphysical Club, the end result is not so much a history of twentieth-century music as a history of the twentieth century through its music.
Keywords: 20th Century (1901-2000); Music history